If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -2(9 + -8x) = 13 -1x + (9 * -2 + -8x * -2) = 13 -1x + (-18 + 16x) = 13 Reorder the terms: -18 + -1x + 16x = 13 Combine like terms: -1x + 16x = 15x -18 + 15x = 13 Solving -18 + 15x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 15x = 13 + 18 Combine like terms: -18 + 18 = 0 0 + 15x = 13 + 18 15x = 13 + 18 Combine like terms: 13 + 18 = 31 15x = 31 Divide each side by '15'. x = 2.066666667 Simplifying x = 2.066666667
| 0=(9-x)(11-2x) | | 2-n=2 | | .3x-.4x-1=3 | | 8x^3-12x^2-8x+1=0 | | -14+6b+7-2v=1+5b | | y=-3y+6 | | 3+x=-4x+18 | | 4r^2-32r+48=0 | | answerto-27-9x=-3(4x+8) | | 32x+12y=420 | | -27-9x=-3(4x+8) | | 15x-6=27x+2 | | 6+3y=-36 | | 8-2x-7x+3= | | 11=r+6 | | .75p-7=11 | | 4a+5b-6a-8b= | | 4-3(x+2)=7(2x+5) | | -145=5(3b-8) | | 3x+4=-5x | | 180=90+3x | | 2t+(3+5t)(4)= | | X^2+3x-195.5= | | 5x+9=2x+13 | | 4-(3x+2)=7(2x+5) | | -4+3x=-6+10 | | -15u-6u-12u-20=13 | | 4x^2+4xy+y^2-100= | | 14.50=p-53 | | X=3y-2400 | | -55-11x=7(9-10x) | | 3x+7y-21=0 |